Positive sentinel lymph node: the evolution of axillary surgery and intraoperative assessment of sentinel lymph nodes. (July 2014) - Rubio, Isabel T; Diaz-Botero, Sebastian; Esgueva, Antonio; Espinosa-Bravo, Martín
SUMMARY : Axillary lymph node dissection (ALND) has been the treatment for breast cancer in patients with sentinel lymph node (SLN) biopsy metastasis for prognostic information, local control and maybe for a small survival benefit. In recent years, clinicians have been questioning the need for axillary dissection in patients with positive SLN as the rate of axillary recurrences remains low when no ALND is performed in this group. Several variables incorporated in nomograms have been examined to predict axillary metastasis in patients with SLN metastasis and these nomograms have helped to determine which patients can spare the morbidity of the ALND. The combined multimodality in breast cancer treatments and the improvement in targeted therapies based in tumor biology have contributed to the low recurrence rates in early-stage breast cancer. As the multimodal treatment and the screening programs will improve, more patients with SLN metastasis will spare an ALND without compromising their oncologic outcome.